Enhancing photoelectrochemical hydrogen production of a n+p-Si hetero-junction photocathode with amorphous Ni and Ti layers. Issue 2 (15th January 2019) - Yu, Chunlin; Jia, Qing; Zhang, Hongxiu; Liu, Wei; Yu, Xuegong; Zhang, Xingwang
Abstract : N + p-Si/Ti/Ni hetero-junction photocathode with high-quality interfaces and light-harvesting capability shows the outstanding PEC-HER performance in alkaline electrolyte. Abstract : Herein, a novel n + p-Si/5 nm Ti/5 nm Ni hetero-junction photocathode was designed and fabricated by coating an amorphous Ti layer (the protection layer) and a Ni layer (the earth-abundant HER catalyst) on mircopyramid-like n + p-Si. We demonstrate its enhanced photoelectrochemical (PEC) hydrogen generation performance with a photocurrent density of −38.7 mA cm −2 at 0 V ( vs. RHE), an onset potential of 0.61 V ( vs. RHE), and an applied bias photon-to-current efficiency (ABPE) of 5.1% under simulated 100 mW cm −2 (1 Sun) with an AM 1.5G filter in 1 M KOH. To the best of our knowledge, this is a new record ABPE for a p-type Si or n + p-Si-based PEC hydrogen generation system. The outstanding performance is attributed to the light-harvesting capability of mircopyramid-like n + p-Si/Ti/Ni, and the high-quality interfaces between each layer of Si/Ti/Ni.